Aerodynamic analysis and modeling of coaxial ducted fan aircraft with the ceiling effect - Tianfu Ai (Taylor & Francis Group, 2021)
In this study, a novel coaxial ducted aircraft structure is considered, based on which the flow field with the ceiling effect under different vertical velocities and heights is obtained by exploiting the CFD (Computational Fluid Dynamics) numerical calculation methods. Taking into account the ceiling effect, a total lift mechanism model of the coaxial ducted aircraft structure is established based on the momentum theory and the blade element theory. In the proposed mechanism model, the relationship between the vertical climbing rate and the induced speed of the rotors and the induced velocity interaction between the coaxial rotors and the effect of the wake of the upper rotor on the lower rotor are considered. To verify the effectiveness and feasibility of the mechanism model, the numerical calculation and the bench test are conducted. The results indicated that, under the hovering condition, the error between the mechanism model and the bench test results falls into 15%; under the vertical climbing condition, the error between the mechanism model and the CFD numerical calculation results falls into 10%. It is concluded that the proposed mechanism model exhibits high adaptability and accuracy.